Insights into Inclusive Growth, Employment and Wellbeing in India - Mitra, Arup.; SpringerLink (Online service) (India : Springer India : Imprint: Springer, 2013)
Arup Mitra is a professor of Economics at the Institute of Economic Growth, Delhi. His research interest include issues in the area of urban development, labour and welfare, industrial growth and productivity and gender inequality. He has published in a number of international and national journals. He worked as a senior researcher at ILO (Geneva), was offered visiting fellowship at Institute of Developing Economies (Tokyo) and held the Indian Economy Chair at Sciences Po. (Paris). The Indian Econometric Society offered him the Mahalanobis Award for his outstanding contribution in the field of quantitative economics. His work has been cited in the Hand Book of Regional and Urban Economics and he has also contributed in the Encyclopaedia of Life Support Systems (EOLSS) and Mathematical Models in Economics (Ed. Zhang, W.), developed under the auspices of the UNESCO.
Keywords: Economics; Development Economics; Endogenous growth (Economics).; Economic policy; Industrial organization (Economic theory).; Labor economics; Social policy; Economics/Management Science; Economic Growth; Development Economics; Economic Policy; Labor Economics; Industrial Organization; Social Policy